Efficiently Guiding K-Robots Along Pathways with Minimal Turns - Hoorfar, Hamid; Taheri, Nedasadat; Kosarirad, Houman; Bagheri, Alireza (EAI Endorsed Transactions on AI and Robotics, 2023)
INTRODUCTION: This paper addresses the navigation of a team of k protector robots within pathways, focusing on minimizing the total number of turns. These robots utilize orthogonal routes known as watchman routes, which prioritize finding the shortest path while maintaining visibility of all points in the environment from at least one robot on its designated route. The main objective of this research is to optimize robot navigation by reducing the overall number of turns.OBJECTIVES: The primary objective of this study is to develop a linear-time algorithm that efficiently processes and determines routes for k robots within a specified area. By minimizing the number of turns, this algorithm aims to enhance the navigation capabilities of watchman robots, enabling them to effectively traverse complex environments.METHODS: This research employs techniques derived from computational geometry to investigate the navigation of protector robots. The focus is on developing an algorithm that can efficiently process and determine the optimal routes for the robots, considering factors such as visibility and shortest path length. The algorithm is designed to minimize the number of turns while ensuring efficient coverage of the environment.RESULTS: The main results of this paper include the development of a linear-time algorithm for determining routes for a team of k protector robots. The algorithm efficiently processes the input data and produces separate routes for each robot. By minimizing the number of turns, the algorithm improves the overall navigation efficiency of the robots. The results demonstrate the effectiveness of the algorithm in optimizing robot paths and reducing the complexity of navigation in real-world scenarios.CONCLUSION: In conclusion, this research contributes to the field of robotic systems by addressing the navigation challenges faced by a team of protector robots. The introduced linear-time algorithm optimizes the routes for k robots, aiming to minimize the total number of turns. The outcomes of this study have significant implications for the advancement of watchman robots, enhancing their coverage and surveillance capabilities in real-world applications. The algorithm’s efficiency and effectiveness in minimizing turns open new opportunities for developing efficient navigation strategies in complex environments.
Keywords: robot navigation; watchman robot; guarding; algorithm; motion planning